Universidade: formação de intelectuais acadêmicos? - Mattos, Priscilla de Cassia Bessi de (2006)
This work has as general objective to analyze the profile assumed for university professors from the areas of social science belonging to the São Paulo State Universities (USP, UNICAMP and UNESP), as well their opinions and reactions a respect of the fast socialeconomic, politic and cultural transformations occurred in the country in the last decades, whose influences reflect incisively on the university institutions and on the positioning of themselves with relation to their proper intellectual condition. In a more specific way we searched during this research to answer the following question: "How the university professors conceive their functions and what type of intellectuals our public universities are forming?" It is a qualitative inquiry based in structuralized open interviews by the way of a script previously elaborated using the research problem. Besides the development of the interviews has became necessary a bibliographical study about intellectuals, culture, university, university professors and society, having as theoretical referential the classic treatment on the elected subjects above, in special, the analysis about the scientific field developed by French sociologist Pierre Bourdieu. The collected data could evidenced that the university professors see themselves as responsible for the critical and for the possible intervention in the society, the academic intellectuals are pointed as those that possess the function to commit themselves to certain practices and try to realize specific changes in the environment in which they are inserted, their work is to be intent to their proper position and how this affects their studies. When describing their functions and reflecting on the university objective in the contemporary society, these protagonists point with respect to the inefficiency of this new model of university, implanted after the University Reformation in 1968, which gives privileges to the scientific and technological development, in order to stimulate the economic growth of the country, for the formation of new generations of intellectuals that, impressionable with the reduction of the time of the intellectual work and the intense production of bureaucratic reports demanded by the State and by the agencies of research promotion, specializes each time more early, disabling a intellectual work, in the sense of critic, reflexive and politician.